2012
DOI: 10.1093/nar/gks257
|View full text |Cite
|
Sign up to set email alerts
|

Human C4orf14 interacts with the mitochondrial nucleoid and is involved in the biogenesis of the small mitochondrial ribosomal subunit

Abstract: The bacterial homologue of C4orf14, YqeH, has been linked to assembly of the small ribosomal subunit. Here, recombinant C4orf14 isolated from human cells, co-purified with the small, 28S subunit of the mitochondrial ribosome and the endogenous protein co-fractionated with the 28S subunit in sucrose gradients. Gene silencing of C4orf14 specifically affected components of the small subunit, leading to decreased protein synthesis in the organelle. The GTPase of C4orf14 was critical to its interaction with the 28S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 38 publications
1
90
0
1
Order By: Relevance
“…It is also known that GTPases are important for mitoribosome assembly, just as they are for bacteria (60). Human NOA1 (hNOA1), also known as MTG3 or C4orf14, is associated with the nucleoid and is necessary for SSU assembly (61)(62)(63). We have also identified ERAL1 in nucleoids (29,64).…”
Section: Discussionmentioning
confidence: 80%
“…It is also known that GTPases are important for mitoribosome assembly, just as they are for bacteria (60). Human NOA1 (hNOA1), also known as MTG3 or C4orf14, is associated with the nucleoid and is necessary for SSU assembly (61)(62)(63). We have also identified ERAL1 in nucleoids (29,64).…”
Section: Discussionmentioning
confidence: 80%
“…Controversially, we noticed a 1.7-fold up regulation after ClpX expression (Table 1). Because NOA1 is an important regulator of mitochondrial function [29][30][31][32]41], we concluded that NOA1 may be transcriptionally up regulated by the UPR mt to compensate for the parallel increase in degradation by the more active ClpXP. Therefore, we screened the noa1 gene promoter for putative CHOP binding sites [8], and we indeed found a putative CHOP consensus sequence (P1) located approximately 400 bp upstream of the initiation codon (Fig 3A).…”
Section: Chop Mediates Clpx-initiated Retrograde Transcriptional Amentioning
confidence: 91%
“…We recently reported a mammalian substrate of ClpXP, the mitochondrial matrix GTPase NOA1 [29][30][31][32]. We showed that increasing ClpX protein levels alone, without changing the ClpP protein level, was sufficient to significantly increase the degradation capacity of the ClpXP complex in vivo [29].…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Currently, very little is known about how assembly of mitoribosomes is achieved, and only a few factors have been identified, which are involved in the assembly of the mt-SSU or mt-LSU (34)(35)(36)(37)(38)(39)(40)(41). Whether AFG3L2 is promoting ribosome formation or stability is at present still unclear.…”
Section: Figurementioning
confidence: 99%